Hymenopteran parasitoids associated with the banana-skipper Erionota thrax L. (Insecta: Lepidoptera, Hesperiidae) in Java, Indonesia - ERNIWATI ERNIWATI; ROSICHON UBAIDILLAH (Biodiversitas Journal of Biological Diversity, 2011)
Erniwati, Ubaidillah R (2011) Hymenopteran parasitoids associated with the banana-skipper Erionota thrax L. (Insecta: Lepidoptera, Hesperiidae) in Java, Indonesia. Biodiversitas 12: 76-85. Hymenopteran parasitoids of banana-skipper Erionota thrax L. (Insecta: Lepidoptera, Hesperiidae) from Java, Indonesia are reviewed and an illustrated key to 12 species is presented to include Theronia zebra zebra, Xanthopimpla gamsura, Casinaria sp., Charops sp., Cotesia (Apanteles) erionotae, Brachymeria lasus, B. thracis, Ooencyrtus pallidipes, Anastatus sp., Pediobius erionotae, Agiommatus sumatraensis and Sympiesis sp. The surveys of the natural enemies of the banana-skipper were conducted in 1990-2006 in several localities in Java. The aim of this study was to assess the native natural enemies of E. thrax, especially the parasitic Hymenoptera. Infested eggs, larvae and pupae of E. thrax were collected and reared in the laboratory. Emerging parasitoids were preserved in both dry mounting and in 80% alcohol for the species identification. Members of families Braconidae, Ichneumonidae, Encyrtidae, Pteromalidae, Chalcididae, Eupelmidae and Eulophidae were recorded as parasitoidsof the banana skipper E. thrax from Java, Indonesia. Species distribution and alternative hosts of the parasitoids are presented.